Philadelphia method as way of rationalization of children with Cerebral Palsy - Kempka-Dobra, Ewa; Steinborn, Barbara (Przewodnik Lekarza/Guide for GPs, 2005)
This work presents development of children with the Cerebral Palsy. One described creature of disease, trick the diagnosis and treatments. Peaceably with foundations methods of Doman, development of child takes place across formation six function of brain: visual, aural, feeling, motorial, lingual and manual. For every child is fixed individual programme of rehabilitation and part of therapists fulfill parents, trained in the Institutes for the Achievement of Human Potential. Peaceably with foundations this of institute one introduced in work: trick of evaluation development of child, programs of reading, increasing of knowledge encyclopaedic and of intelligence and programme of development motorial.